Sistem Pendukung Keputusan Pemilihan Jasa Travel Menggunakan Metode Multi Attribute Utility Theory - Pasha, Donaya (Jurnal Ilmiah Computer Science, 2024)
Decision Support System (DSS) is an information system designed to assist decision makers in the process of data analysis and evaluation of alternatives to achieve certain goals. This study aims to determine travel services using the Multi Attribute Utility Theory method so that the results of recommendations can be input for users in selecting existing travel services. With this decision support system, it is expected that the process of selecting travel services will not only be more efficient but also provide a more satisfying travel experience for customers. The final ranking results were ranked 1st with a value of 0.678062574 obtained by Travel E, rank 2nd with a value of 0.459657989 obtained by Travel D, and rank 3rd with a value of 0.42685178 obtained by Travel C.